Особливості становлення й розвитку етнографічного музейництва на півдні України в ХІХ — на початку ХХ ст. - Величко, Т. (Народна творчість та етнографія, 2008)
The article is dedicated to the problem of the ethnographic research foundation in the South Ukraine in the 19th century as well as the process of ethnographic museums formation from the generation of ethnographic monuments collection to creation of the first museum centers of ethnographic type. By the example of the activity of museums of the 19th century and the beginning of the 20th century in Odesa oblast and the Crimea the author determines regional peculiarities of museum ethnography in Novorosiysky krai.